The Influence of Brand Love and Hedonistic Lifestyle on the Purchasing Decision of Iphone Smartphones (A Study on Iphone Users From Generation Z in Surabaya) - Mohammad Farraas Salsabiil; Nuruni Ika Kusuma W (Indonesian Journal of Business Analytics, 2023)
This study aims to analyze the effect of brand love and hedonistic lifestyle on iPhone smartphone purchasing decisions in Surabaya. Based on the research results of 119 respondents, love for the brand and a hedonistic lifestyle positively and significantly affect the decision to buy an iPhone smartphone. The push variable of brand love is the most significant factor in influencing consumers' purchasing decisions. At the same time, the indicator of a hedonistic lifestyle is the distribution of buying ideas or consumers' level of knowledge about the latest trends, fashions, and innovations. In this context, brand love and a hedonistic lifestyle are important factors in attracting and influencing consumers' purchasing decisions for iPhone smartphone products. This research aligns with previous research showing a positive and significant effect of brand love and a hedonistic lifestyle on product purchasing decisions.